2022
DOI: 10.1111/bph.15903
|View full text |Cite
|
Sign up to set email alerts
|

β‐Arrestin‐biased proteinase‐activated receptor‐2 antagonist C781 limits allergen‐induced airway hyperresponsiveness and inflammation

Abstract: Background and Purpose Asthma is a heterogenous disease strongly associated with inflammation that has many different causes and triggers. Current asthma treatments target symptoms such as bronchoconstriction and airway inflammation. Despite recent advances in biological therapies, there remains a need for new classes of therapeutic agents with novel, upstream targets. The proteinase‐activated receptor‐2 (PAR2) has long been implicated in allergic airway inflammation and asthma and it remains an intriguing tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…It is unlikely that the compound is metabolized in the liver because C781 has a long half-life in liver microsomes. Our pharmacological study should be viewed as proof of concept for the efficacy of a PAR2 antagonist that selectively blocks β-arrestin signaling downstream of the receptor for the treatment of CIPN 78 . Future development of similar PAR2 antagonists with a more favorable pharmacokinetic profile will allow for longer target coverage in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unlikely that the compound is metabolized in the liver because C781 has a long half-life in liver microsomes. Our pharmacological study should be viewed as proof of concept for the efficacy of a PAR2 antagonist that selectively blocks β-arrestin signaling downstream of the receptor for the treatment of CIPN 78 . Future development of similar PAR2 antagonists with a more favorable pharmacokinetic profile will allow for longer target coverage in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel was injected into the peritoneal space using a 27G ½” needle. C781 was synthesized using solid-phase synthesis as described previously 78 . C781 was injected into the peritoneal space using a 27G ½” needle at a dosage of 10 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study, a Par2 antagonist (C391) was proven to block Par2 signaling induced by the fungi [ 20 ]. A follow-up investigation showed that the antagonist C781, when given prophylactically, alleviated airway inflammation and mucus overproduction of the small airways in an acute allergen-challenged mouse model induced by Alternaria alternata [ 108 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing these reports based on the tissues in which Par2 is predominantly activated, the seeming contradictions can be resolved. When the immune system is activated, as in the cases of cockroach extract, HDM extract, Alternaria alternata, Streptococcus pneumoniae, and LPS, Par2 activation in immune cells leads to the aggravation of the asthmatic and inflammatory phenotypes [ 8 11 , 20 , 105 108 , 111 ]. These asthma and inflammatory experiments were validated by the secretion of interleukins and chemokines, inflammatory markers, the presence of different leukocyte populations in the BAL, and the amount of secreted mucus.…”
Section: Introductionmentioning
confidence: 99%